News from the British Renal Society. (2nd March 2019) - Jenkins, Karen
Abstract : In this article, Karen Jenkins, British Renal Society Vice President Clinical Practice, outlines what you can expect from UK Kidney Week. We celebrate the winner and finalists of the Renal Nurse of the Year 2019 award and include an update on the joint patient safety committee